ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU TETAP YAYASAN (Studi Kasus Pada SMP Mawar Sharon Christian School Surabaya) - Aryo Putra Ardhitianto; Fariz Fariz (ITB AAS Indonesia Surakarta, 2023)
This study aims to determine the factors that influence teacher performance at SMP Mawar Sharon Christian School Surabaya. This study uses a quantitative approach. The study population was 26 permanent teachers at the SMP Mawar Sharon Christian School Surabaya. The data collection technique uses a questionnaire through the Google form. Data analysis techniques using multiple linear regression, F test, and t test. Based on the results of the study it is revealed that the work environment influences teacher performance, this shows that the better the work environment, the teacher's performance will still increase. Motivation affects teacher performance, this shows that the more teacher motivation increases, the teacher's performance will still be higher. Leadership affects teacher performance, this shows that the better the leadership of the principal, the higher the teacher's performance. Training has an effect on teacher performance, this shows that the more often training is carried out by teachers, the higher teacher performance will still be.